(untitled) (Medical Forum Monthly, 2024)
ABSTRACT Objective: To find out the seroprevalence of Hepatitis B Virus Antigen (HBs Ag) detected during blood screening in the candidates of recruitment in Armed forces of Pakistan from Southern Punjab. Study Design: Observational study Place and Duration of Study: This study was carried out at the Department of Pathology, Combined Military Hospital (CMH), Multan from January to December 2013. Materials and Methods: Serological blood screening of blood donors and candidates coming for recruitment in armed forces of Pakistan at CMH Multan was performed. Test was performed with rapid screening kit initially and suspected cases were confirmed with third generation ELISA technique. Bio-data of Hepatitis B virus Antigen (HBs Ag) positive cases was collected, analyzed and compared with national and international literature. Results: A total of 10666 persons were screened out, 388 (3.63%) were HBs Ag positive. Conclusion: Seroprevalence of HBs Ag in this region is also high like rest of the world. Public awareness about the disease, prophylactic vaccination against hepatitis B, blood screening before transfusion, use of disposable syringe, proper disposal of contaminated material and prevention from sexual transmission are required to decrease the incidence and its spread.